Assessing progress on the coverage of interventions in the first 1000 days in India: Role of national programs - Avula, Rasmi; Nguyen, Phuong Hong; Christopher, Anita; Gune, Soyra; Bhatia, Neena; Chauhan, Alka; Dwivedi, L. K.; Kapur, Avani; Pedgaonkar, Sarang; Shukla, Ritwik; Chakrabarti, Suman; Singh, Shri Kant; et al. (BMJ, 2024)
Background High coverage of nutrition-specific interventions is critical to meet global nutrition targets, and it is imperative to understand how to attain it. We examined trends and inequalities in the coverage of interventions in India and the role of the National Nutrition Mission (NNM) in achieving improvements.